Pengaruh Fasilitas Belajar, Motivasi Belajar dan Manajemen Kelas terhadap Hasil Belajar Siswa - Aryati Puspa Dewi; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This research aims to determine the influence of learning facilities (X1), learning motivation (X2) and classroom management (X3) on student learning outcomes (Y). This research uses quantitative techniques with descriptive analysis. Data collection was carried out through filling out questionnaires. The subjects of the research were general students, totaling 151 respondents. In analyzing the results of this research, a tool was used in the form of Partial Least Square Software (SmartPLS 4.0). The research results show that: 1) Learning facilities have a positive effect on student learning outcomes; 2) Learning motivation has a positive effect on student learning outcomes; 3) Class management has a positive effect on student learning outcomes.